Increasing postural deformity trends and body mass index analysis in school-age children - Kapo, Safet (Zdravstveno varstvo, 2018)
Introduction: The aim of the study was to analyse the deviations of the body posture and to assess the occurrence of spine deformities. Additionally, Body Mass Index in school children was related to the trend in postural deformities for different age groups (5-8 years old, n=112; 9-11 years old, n=205; 12-14 years old, n=212) as part of the project %Spine Lab%, granted from the European Commission IPA founds, investigating the importance of public health issues. Methods: Body posture was measured using Contemplas 3D software analyser, based on video image trajectory and BIA weight scale (Tanita BC 420). Overall, 17 variables were assessed, and differences were confirmed using MANOVA analysis. Results: The results showed that there is a significant difference between age groups for the measured variables (F=9.27; p<0.01; %2=0.26), suggesting a moderate difference across the age span. Conclusion: The study results showed that there is a negative trend of increasing Body Mass Index within the first and youngest age group. The fact is that the trend of increasing deformity of the shoulder belt has been noted, often inclining towards the formation of milder forms of kyphotic posture. Other forms of deformity that are accentuated in the survey results are the negative trend of increasing pelvic rotation and pelvis rotation which inclines towards the formation of lordotic posture for all three age group
Keywords: javno zdravje; presejalni testi hrbtenjače; prevalence rate; public health; spinal screening; spremembe v trendih; stopnja razširjenosti; trend changes